The Influence of Emotional Intelligence and Work Life Balance on Employee Performance in the Central Tapanuli Regency Government - Lubis, Fajar; Tanjung, Mansur (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2024)
Several internal and external factors influence a company's ability to improve employee performance. Involving what are regarded as internal organizational aspects, such as work-life balance and emotional intelligence. Thus, this study aims to determine whether the Central Tapanuli Regency government influences work-life balance and emotional intelligence. In this study, survey-based quantitative methodologies were employed to collect data. The study's findings demonstrate that work-life balance and emotional intelligence significantly affect employees' performance in the Central Tapanuli Regency Government. Therefore, the Central Tapanuli Government must know these factors to support staff performance.